Spontaneous symmetry breaking in the theory of modulated structures - Babich, A.V.; Berezovsky, S.V.; Klepikov, V.F. (Вопросы атомной науки и техники, 2007)
The parametrical evolution of the one-component order parameter under the spontaneous symmetry breaking in the Michelson model is considered. A critical behavior of a system with the critical point which has the properties of both the Lifshitz point of arbitrary order and the multicritical point is investigated. Critical dimension of such systems was found. The scale variational invariance of the model is discussed. Розглянуто параметричну еволюцію однокомпонентного параметра порядку при спонтанному порушенні симетрії в моделі Міхельсона. Для моделі, яка дозволяє описувати фазові перетворення поблизу точок, які водночас мають властивості точок Ліфшиця довільного порядку і мультикритичних точок, знайдено критичну розмірність. Обговорюється варіаційна масштабна симетрія для таких моделей. Рассмотрена параметрическая эволюция однокомпонентного параметра порядка при спонтанном нарушении симметрии в модели Михельсона. Для модели, позволяющей описывать фазовые переходы вблизи критических точек, обладающих одновременно свойствами точек Лифшица произвольного порядка и мультикритических точек, найдена критическая размерность. Обсуждается вариационная масштабная симметрия для таких моделей.